BIL Bibliografia Informatizzata Leopardiana 1815-1999: manuale d'uso ver. 1.0 - Simone, Magherini (Strumenti per la didattica e la ricerca, 2003)
The Bibliografia Informatizzata Leopardiana (BIL) is the result of a research project that took shape on the occasion of the second centenary of the birth of the poet and developed over the span of 2000-2002. The project envisioned the organisation and publication in a digital corpus of the vast bibliography on Leopardi, up to then disseminated not only in the volumes of the Bibliografia leopardiana, but also in other partial bibliographies, indices, catalogues etc. Implementation of the project engaged four Research Units from the universities of Florence, Macerata, Cagliari, and Rome «La Sapienza». The book contains the User Manual for the BIL (version 1.0) and the description of the project.